PARTICIPATION OF NURSES IN ANTIMICROBIAL STEWARDSHIP PROGRAMS: AN INTEGRATIVE REVIEW - Adriana Maria da Silva Felix; Sandra Regina Toffolo (Universidade Federal do Paraná, 2019)
Objective: To investigate publications in the literature on the participation of nurses in antimicrobial stewardship programs. Method: Integrative review with search in the following databases: the Medical Literature Analysis and Retrieval System Online, the Latin American and Caribbean Center on Health Sciences Information, and the Cumulative Index to Nursing and Allied Health Literature. As inclusion criteria, full articles in Portuguese, English, or Spanish published between January 2007 and May 2018 were selected.Results: Of the 140 articles found, 12 met the inclusion criteria, and were organized into the following three categories: "nurses' competencies in antimicrobials stewardship programs" (five articles), "lack of knowledge and need for training" (six articles), and "systemic action" (one article). Conclusion: Nurses may contribute significantly to antimicrobial stewardship programs; however, educational actions, studies, and public policies are necessary for their effective participation.